(untitled) (Annals of Medical Research, 2021)
Aim: This study aims to investigate anthelmintic effect of the essential oil and crude extract of Salvia sclarea L.,Lamiaceae (clary sage), which are widespread in the region of Julfa and Kangarlı districts in Nakhchivan Autonomous Republic. The essential oil was extracted from top flowers and fresh leaves of the plant by ether distillation. Crude extracts were prepared by boiling the dry parts of the plant. Than the extracts were administered separately, in vivo and in vitro targeting on the nematodes localized in the digestive tract of sheep. The results revealed that both extracts have strong anthelmintic effect on nematodes.Material and Methods: The essential oil output of the plant was found to be 0.3-0.4%. The composition of the essential oil was further analyzed by gas chromatography. Total 26 different substances were identified 26 in essential oil extract. Linalylacetate (41.2%) and linalool (18.9%) were found to be the major components of essential oil, extracted from the clary sage.Results: The success in the treatment of nematodes (intensive efficacy) in vivo was 84.3% for essential oil extract, and 69.4% for the crude extract of clary sage species. The extensive efficacies of both products were found to be 60% and 40% respectively. Conclusion: The results confirm that clary sage has high anthelmintic effect in vivo and in vitro on gastrointestinal nematodes in sheep.